mTOR Complex 2 Targets Akt for Proteasomal Degradation via Phosphorylation at the Hydrophobic Motif - Wu, You-Tong (American Society for Biochemistry and Molecular Biology, 2011)
The protein kinase Akt (also known as protein kinase B) is a critical signaling hub downstream of various cellular stimuli such as growth factors that control cell survival, growth, and proliferation. The activity of Akt is tightly regulated, and the aberrant activation of Akt is associated with diverse human diseases including cancer. Although it is well documented that the mammalian target of rapamycin complex 2 (mTORC2)-dependent phosphorylation of the Akt hydrophobic motif (Ser-473 in Akt1) is essential for full Akt activation, it remains unclear whether this phosphorylation has additional roles in regulating Akt activity. In this study, we found that abolishing Akt Ser-473 phosphorylation stabilizes Akt following agonist stimulation. The Akt Ser-473 phosphorylation promotes a Lys-48-linked polyubiquitination of Akt, resulting in its rapid proteasomal degradation. Moreover, blockade of this proteasomal degradation pathway prolongs agonist-induced Akt activation. These data reveal that mTORC2 plays a central role in regulating the Akt protein life cycle by first stabilizing Akt protein folding through the turn motif phosphorylation and then by promoting Akt protein degradation through the hydrophobic motif phosphorylation. Taken together, this study reveals that the Akt Ser-473 phosphorylation-dependent ubiquitination and degradation is an important negative feedback regulation that specifically terminates Akt activation.